Children's Active Commuting to School: Current Knowledge and Future Directions - Kirsten K. Davison, PhD; Jessica L. Werder, MPH; Catherine T. Lawson, PhD (Centers for Disease Control and Prevention, 2008)
IntroductionDriven largely by international declines in rates of walking and bicycling to school and the noted health benefits of physical activity for children, research on children's active commuting to school has expanded rapidly during the past 5 years. We summarize research on predictors and health consequences of active commuting to school and outline and evaluate programs specific to children's walking and bicycling to school.MethodsLiterature on children's active commuting to school published before June 2007 was compiled by searching PubMed, PsycINFO, and the National Transportation Library databases; conducting Internet searches on program-based activities; and reviewing relevant transportation journals published during the last 4 years. ResultsChildren who walk or bicycle to school have higher daily levels of physical activity and better cardiovascular fitness than do children who do not actively commute to school. A wide range of predictors of children's active commuting behaviors was identified, including demographic factors, individual and family factors, school factors (including the immediate area surrounding schools), and social and physical environmental factors. Safe Routes to School and the Walking School Bus are 2 public health efforts that promote walking and bicycling to school. Although evaluations of these programs are limited, evidence exists that these activities are viewed positively by key stakeholders and have positive effects on children's active commuting to school.ConclusionFuture efforts to promote walking and bicycling to school will be facilitated by building on current research, combining the strengths of scientific rigor with the predesign and postdesign provided by intervention activities, and disseminating results broadly and rapidly.